Medijske podobe ljudi z ovirami - Kapus, Andraž (Socialno delo, 2014)
The research presented in this paper explored the representation of people with disabilities in three most circulated Slovenian daily payable newspapers in 2012. The content and discourse analysis focused on language, headlines, visual data and content. The results indicate that the representations of people with disabilities are stereotyped and stigmatizing. People's impairments are often in the function of symbolical representation of misfortune and bad social conditions. Impairments are also used to sensationalize the content of the articles. Results show that people with disabilities are most often seen as the object and not as the subject of help. Critical articles debate diverse topics concerning disability but rarely question the existing system of help which lacks individualization and opportunities.
Keywords: hendikep; invalidi; Slovenia; Slovenija; mediji; communication medium; časnikarski jezik; stereotipi; doskriminacija; pomoč; stigma